ChemInform Abstract: Thiyl Radicals: From Simple Radical Additions to Asymmetric Catalysis. Issue 9 (March 2015) - Subramanian, Hariharaputhiran; Moorthy, Ramkumar; Sibi, Mukund P.
Abstract Review: 8 refs.